The Family Division of Labour - Tremblay, Diane-Gabrielle (Relations industrielles / Industrial Relations, 2002)
The Family Division of Labour, by Marie-Agnes Barrere-Maurisson, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Families & family life; Housework; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work & family; Working conditions